Ludo in Art of Beat Style - Triana Martasya Andini; Fendi Nofrian; Nofi Rahmanita; Mirda Aryadi (INDO PUBLISHING, 2026)
This work, entitled “Ludo in Art of Beat Style,” is inspired by the game of Ludo as a source of ideas for fashion creation based on the Art of Beat style. Ludo was chosen because of its strong visual characteristics, including geometric shapes, symmetrical patterns, and contrasting primary colors, namely red, yellow, green, and blue. These characteristics were developed into expressive, creative, and artistic fashion designs in accordance with the Art of Beat Style concept, which emphasizes freedom of expression, uniqueness, and an anti-mainstream character. The creation method consisted of several stages, namely exploration, design, and realization. The exploration stage involved observing the Ludo game and Art of Beat fashion style. The design stage included the creation of a moodboard, alternative sketches, and selected designs, while the realization stage involved the construction of garments through the application of fabric appliqué techniques, material selection, and the implementation of design elements and principles. The results of this creation consist of three fashion levels: Ready-to-Wear, Ready-to-Wear Deluxe, and Haute Couture. Each work presents the visual characteristics of Ludo combined with the Art of Beat style, resulting in unique and dynamic garments with high aesthetic value.